MENGGAMBAR DARI ANGKA BAGI GURU TK UMP - Lia Mareza; Agung Nugroho (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
Activities to produce a work of art is a process that requires sensitivity to the object as a work activity creates. Drawing is part of the global movement for children's motor, the whole body is involved in the drawing. Although graffiti children aged under five can not be called an image but in a later stage, the resulting strokes will be meaningful for children and parents. Drawing is the stage after passing through the stage of the graffiti-crossed. Phase drawing, children do work that involves coordination from imagination, hands, eyes and other body parts. The training was attended by 11 teachers in the UMP kindergarten. Training results showed an increase in terms of composition and creativity of teachers in the drawing of the numbers. Keywords: drawing, figure, art